Kebijakan Pengembangan Koleksi di Perpustakaan Khusus Balai Besar Pelatihan Pertanian Lembang - Harsendiana, Rega; Djuwariah, Siti (Program Studi Ilmu Perpustakaan dan Informasi, Universitas Islam Nusantara, 2024)
This study examined the collection development policy at the Special Library of the Lembang Agricultural Training Center, aiming to understand how collection development met the diverse information needs of its users. Based on Indonesian Law No. 43 of 2007, libraries played a crucial role in managing collections for education, research, and information dissemination. This research applied a qualitative method to explore users' perspectives on the available collection. The findings showed that users consisted of university students, vocational school students, and employees, each with different information needs. The existing collection development policy served as a guideline for the selection and acquisition of library materials, ensuring relevance and quality. Collection development was not limited to printed formats but also included digital materials for more flexible access to information. This study emphasized the importance of regular evaluations to identify the strengths and weaknesses of the collection and to understand users' needs in depth. As a recommendation, it was suggested that the library adapt to technological developments and strengthen collaboration with other institutions to enhance the quality of information services. These efforts were expected to ensure that the collection remained relevant and met the information needs of the agricultural community.